Diseases of fruit crops in Australia - Cooke, Tony, 1954-; Persley, Denis M.; House, Susan (CSIRO Pub., 2009)
Diseases of Fruit Crops in Australia is the new standard reference in applied plant pathology in Australia covering important diseases affecting the broad range of fruit and nut crops grown throughout Australia. It is an essential tool for growers, horticulturists, crop consultants, research scientists, plant pathologists, quarantine officers, agribusiness representatives, pest management personnel, educators and students. The book is generously illustrated with high quality colour images to help diagnose diseases and explains how to identify and manage each disease, describing the symptoms of.